Intra-Arterial Therapy and Post-Treatment Infarct Volumes: Insights From the ESCAPE Randomized Controlled Trial. Issue 3 (March 2016) - Al-Ajlan, Fahad S.; Goyal, Mayank; Demchuk, Andrew M.; Minhas, Priyanka; Sabiq, Farahna; Assis, Zarina; Willinsky, Robert; Montanera, Walter J.; Rempel, Jeremy L.; Shuaib, Ashfaq; Thornton, John; Williams, David; et al.
Abstract : Background and Purpose—: The goal of reperfusion therapy in acute ischemic stroke is to limit brain infarction. The objective of this study was to investigate whether the beneficial effect of endovascular treatment on functional outcome could be explained by a reduction in post-treatment infarct volume. Methods—: The Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Times (ESCAPE) trial was a multicenter randomized open-label trial with blinded outcome evaluation. Among 315 enrolled subjects (endovascular treatment n=165; control n=150), 314 subject's infarct volumes at 24 to 48 hours on magnetic resonance imaging (n=254) or computed tomography (n=60) were measured. Post-treatment infarct volumes were compared by treatment assignment and recanalization/reperfusion status. Appropriate statistical models were used to assess relationship between baseline clinical and imaging variables, post-treatment infarct volume, and functional status at 90 days (modified Rankin Scale). Results—: Median post-treatment infarct volume in all subjects was 21 mL (interquartile range =65 mL), in the intervention arm, 15.5 mL (interquartile range =41.5 mL), and in the control arm, 33.5 mL (interquartile range =84 mL; P <0.01). Baseline National Institute of Health Stroke Scale ( P <0.01), site of occlusion ( P <0.01), baseline noncontrast computed tomographic scan Alberta Stroke Program Early CT score (ASPECTS) ( P <0.01), and recanalization ( P <0.01) were independently associated with post-treatment infarct volume, whereas age, sex, treatment type, intravenous alteplase, and time from onset to randomization were not ( P >0.05). Post-treatment infarct volume ( P <0.01) and delta National Institute of Health Stroke Scale ( P <0.01) were independently associated with 90-day modified Rankin Scale, whereas laterality (left versus right) was not. Conclusions—: These results support the primary results of the ESCAPE trial and show that the biological underpinning of the success of endovascular therapy is a reduction in infarct volume. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01778335.